PENGARUH PENGUMUMAN DIVIDEN TERHADAP ABNORMAL RETURN DAN LIKUIDITAS SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (STUDY KASUS KELOMPOK PERUSAHAAN LQ-45 PERIODE FEBRUARI SAMPAI JULI 2013) - Surya Aji Sambodo; Yulia Efni; Edyanus Herman Halim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research to determine the difference abnormal return and liquidity of shares before and after the announcement of the dividend on the company group LQ-45 period February to July 2013. This research was conducted by using a population that LQ-45 period from February to July 2013 with a sample of 43 companies that conduct is declared in the period 2009-20012 in Indonesia Stock Exchange (IDX). While the analysis tool used is One sample T-test and paired sample t-test. From the results of the testing that has been done, it is evident that in the aggregate showed that there was no significant difference between the abnormal returns before and after the dividend announcement. Likewise, trading volume activity showed that no significant difference between the average abnormal volume before and the average abnormal volume after announcement.Keywords: Dividen annoucement, Average Abnormal Return, Average trading volume activity